Inoculum and inoculation techniques: key steps in studying pathogenicity and resistance to Sclerotinia stem rot in oilseed rape - Zamani-Noor, Nazanin; Jedryczka, Malgorzata (Frontiers in Plant Science, 2025)
Sclerotinia sclerotiorum is a soilborne and necrotrophic fungal pathogen that causes substantial yield and economic losses in oilseed rape cultivation worldwide. To date, no immune oilseed rape germplasm has been identified, posing a major challenge for breeding resistance to Sclerotinia stem rot. Developing reliable assessment techniques to evaluate oilseed rape resistance to the disease is a critical step in investigating genetic control and producing resistant cultivars. Extensive evaluations of oilseed rape genotypes have been conducted under both field and controlled conditions to assess resistance to Sclerotinia stem rot. Most inoculation techniques employ mycelium or mycelium-colonized substrates such as agar plugs, cereal grains, toothpicks, or petals. The use of ascospores as inoculum has been less common, despite their important role in the natural infection cycle. Several inoculation methodologies for controlled environments have been developed and evaluated for screening oilseed rape germplasm, including detached leaf/stem assays, intact leaf assays, cotyledon screening, as well as petiole and leaf axil inoculation. In parallel, several methods have been developed to assess Sclerotinia resistance under field conditions, such as intact stem inoculation at the flowering or maturity stage using S. sclerotiorum-infested toothpick, spraying ascospore suspensions onto plants, and spreading S. sclerotiorum-infested wheat grains. This review explores the suitability of various S. sclerotiorum inoculum types and evaluates the most common inoculation techniques for effective identification of susceptible and resistant oilseed rape genotypes to Sclerotinia stem rot.